Resiliensi Guru yang Mengajar di Panti Asuhan Al-Mizan Muhammadiyah Lamongan - Yusnia Rahayu; Prianggi Amelasasih (PT. Penerbit Tiga Mutiara, 2025)
An orphanage is a social institution that functions to provide protection, care, and guidance for children who have lost the support of their nuclear families. Its role is not limited to fulfilling basic needs but also contributes significantly to education and character development. Teachers working in orphanages face dual roles as educators and caregivers, requiring psychological resilience to manage emotional pressures, limited resources, and the complexity of social relationships in the workplace. In this context, resilience becomes a key factor that enables teachers to adapt, overcome obstacles, and develop effective strategies to maintain both personal and professional stability. This study aims to describe teacher resilience at Muhammadiyah Orphanage Lamongan using a qualitative approach with a case study design. The research subjects consisted of two teachers, with data collected through in-depth interviews and participatory observation, supported by triangulated information from significant others. The findings indicate that both subjects experienced resilience dynamics due to dual roles and adaptation difficulties, particularly in time management and task distribution. Nevertheless, strategies such as effective time management, utilization of social support, and reflective ability in interpreting experiences proved to be essential factors in strengthening their resilience. The study concludes that teacher resilience in orphanages is an adaptive process shaped by the interaction of personal, social, and contextual factors. Therefore, institutional interventions in the form of self-management training and enhanced environmental support are necessary to ensure the sustainability of teachers’ roles in orphanages.